PERANCANGAN INFOGRAFIS “KENALAN DULU YUK DENGAN INDUSTRI 4.0” SEBAGAI MEDIA INFORMASI KONDISI DUNIA KERJA KEPADA PELAJAR OLEH KEMENTERIAN PERINDUSTRIAN - Cempaka, Gilang (Kartala, 2022)
Digital technology today has become integral aspect in our daily life. This advanced technology, which also called industry 4.0, disrupt how things work in almost everything in life, such as how we do our jobs. Some jobs have become irrelevant, but new kinds of jobs also emerge as the technology continues to grow. These new jobs required a new set of skills to master, so new workforce candidates could survive and thrive. But in fact many Indonesian worker still don’t have those digital skills, nor able use it to help them to do their job. One of the important aspects that led to this problem is that the students were under informed and lacked a socialization program about today’s world of work. Therefore, to answer this concerns, author and Ministry of Industry of Indonesia, as a government stakeholder responsible of preparing workforces with high competencies in industry4.0 sectors, create program to inform high school students regarding to this world of work condition in industry 4.0 ages topic through infographics, as well as to do a socialization campaign to spread out the informations even further. Hopefully with this infographics and socialization campaign, high school students as new workforce candidate will have awareness and knowledge about this phenomenon, and they will be able to make an informed decision to wisely choose their career path.